Prevalence of suicide ideation and attempts among Black Americans in later life. (April 2014) - Joe, Sean; Ford, Briggett C.; Taylor, Robert Joseph; Chatters, Linda M.
This article provides the first national estimates of the prevalence and correlates of nonfatal suicidal behavior among older Black Americans. There is a lack of national data on suicide ideation and attempts across ethnic classifications of Blacks in a nationally representative sample. Data are a subsample from the National Survey of American Life (NSAL), a national U.S. adult household probability sample of 5, 191 Black Americans. The WHO Composite International Diagnostic Interview (CIDI) was used to assess older Blacks for nonfatal suicidal behavior and 14 DSM-IV disorders. Bivariate and multivariate logistic regression analyses were employed to delineate patterns and correlates of nonfatal suicidal behavior. The estimated lifetime prevalence of suicidal ideation and attempts among older Blacks in the United States was 6.1% and 2.1%, respectively. On an average it took 2.5 and 5.7 years respectively to go from ideation to attempts or from planning to attempts. Surprisingly, among older Black adults, men reported attempting suicide and seriously consider taking their own lives more than women. Older Blacks at higher risk for suicide attempts were middle aged, had poorer health, were anxious, and had multiple DSM-IV disorders. The results also show that approximately 1 in 4 attempters and 2 in 5 ideators have never sought treatment for their emotional or psychological problems. Preventative care, particularly screening in primary care settings, should consider these findings when treating older Black Americans for psychiatric-related risk.